ETNOBOTANI REMPAH TRADISIONAL DI DESA EMPOTO KABUPATEN SANGGAU KALIMANTAN BARAT - Robi, Yohanes; Kartikawati, Siti Masitoh; Muflihati, . (Universitas Tanjungpura, 2019)
This study examines the ethnobotany of traditional spices in the Village of Empoto, Sanggau District, West Borneo. The research was conducted by interviewing, observing and making herbarium specimens. This study aims to record the plants spesies used as traditional spices, and explore the Â patterns utilization of plants as traditional spices by the pople in the village of Empoto, Sanggau District, West Kalimantan. As many as 59 plants species from 27 families are traditionaly used by the communities in Empoto village as traditional spices. The most widely used of plant family is Zingiberaceae (8 species). The highest utilization of plants as spices are derived from Dayak tribe, followed by Malay tribe and simultaneous utilization of this both tribe, (100%, 28% and 28% respeetively). The pattern of utilization of spices used by the poeple in Empoto Village, Sanggau District,West Kalimantan is grouped into 7 patterns, namely spices as spices, flavour enhancers, aromatics, preservatives, naturalizers, softeners and coloring.Keywords : Empoto Village, Ethnobotany, Traditional Spices